The Deposition of Cholesterol in Blood Vessels May Lead to Blood Clotting: Coronary Artery Disease - Mastoi, S. Murad (International Journal of Pharmaceutical & Biological Archive, 2023)
In the body, liver produces approximately 80% of the cholesterol whereas rest of the cholesterol is obtained from the food such as fish, eggs, and meat. After having a meal, cholesterol is digested and absorbed in small intestine then the metabolism and storage occurred in the liver. The cholesterol may be secreted by the liver whenever the requirement of cholesterol is needed by the body. Cholesterol is not present in the food which is derived from the plants. We in this study have compared hypolipidemic effects of Fenugreek, Curcuma longa, and Lemon. The study was conducted at Jinnah Hospital Lahore-Pakistan from January to May 2019.